IMPACT OF INTERNAL AUDIT ON FINANCIAL STATEMENT QUALITY OF CHINA'S SME BOARD - Xu FuPing; Ooi Kok Loang (International Journal of Accounting, Finance and Business, 2023)
This paper focuses on the impact of internal audit quality on the quality of financial statement information. This study constructs an evaluation system for the quality of internal audit of enterprises by selecting five independent variables: the scale of internal audit, audit capability, scope of internal audit function, reliability of internal audit system, and independence of internal audit firms, and the dependent variable is selected as a proxy variable for the quality of financial statements of enterprises whether financial restatement occurs. The final sample data selected was for 50 Chinese SME financial services sector listed companies. The data range is from 1 January, 2019 to 31 December, 2021. By building a model, using linear regression to effectively analyse the above variables, and testing the proposed hypothesis, it is finally concluded that internal audit quality is positively related to financial statements. In other words, the higher the quality of a company's internal audit, the higher the quality of its financial statements. This study helps provide scholars with some ideas on selecting quantitative internal audit quality indicators when studying the impact of internal audit quality on financial statement quality. It guides for companies to improve the quality of their financial statements by optimising the quality of internal audits.